Leaf Area and Structural Changes after Thinning in Even-Aged Picea rubens and Abies balsamea Stands in Maine, USA - R. Justin DeRose; Robert S. Seymour (International Journal of Forestry Research)
We tested the hypothesis that changes in leaf area index (LAI m2 m−2) and mean stand diameter following thinning are due to thinning type and residual density. The ratios of pre- to postthinning diameter and LAI were used to assess structural changes between replicated crown, dominant, and low thinning treatments to 33% and 50% residual density in even-aged Picea rubens and Abies balsamea stands with and without a precommercial thinning history in Maine, USA. Diameter ratios varied predictably by thinning type: low thinnings were <0.7, crown thinnings were >0.7 but <1.0, and dominant thinnings were >1.0 . LAI change was affected by type and intensity of thinning. On average, 33% density reduction removed <50% of LAI, whereas 50% density reduction removed >50% of LAI. Overall reduction of LAI was generally greatest in dominant thinnings (54%), intermediate in crown thinnings (46%), and lowest in low thinnings (35%). Upon closer examination by crown classes, the postthinning distribution of LAI between upper and lower crown classes varied by thinning history, thinning method, and amount of density reduction.